Neoadjuvant chemotherapy in locally advanced colon cancer. A phase II trial. (26th November 2015) - Jakobsen, Anders; Andersen, Fahimeh; Fischer, Anders; Jensen, Lars H.; Jørgensen, Jens C. R.; Larsen, Ole; Lindebjerg, Jan; Pløen, John; Rafaelsen, Søren R.; Vilandt, Jesper
Abstract : Background. Neoadjuvant chemotherapy has proven valuable in several tumors, but it has not been elucidated in colon cancer. The present phase II trial addressed the issue in high-risk patients selected by computed tomography (CT) scan. Material and methods. Patients with resectable colon cancer fulfilling the following criteria were offered inclusion; Histopathological verification of adenocarcinoma, T3 tumor on CT scan with extramural tumor invasion > 5 mm or T4 tumor, age ≥ 18 years, PS ≤ 2, adequate hematology, and informed consent. Patients with KRAS, BRAF or PIK3CA mutation or unknown mutational status received three cycles of capecitabine 2000 mg/m 2 days 1-14 q3w and oxaliplatin 130 mg iv day 1 q3w. Wild-type patients received the same chemotherapy supplemented with panitumumab 9 mg/kg iv q3w. After the operation, patients fulfilling the international criteria for adjuvant chemotherapy, i.e. high-risk stage II and III patients, received five cycles of the same chemotherapy without panitumumab. Patients not fulfilling the criteria were offered follow-up only. The primary endpoint was the fraction of patients not fulfilling the criteria for adjuvant chemotherapy (converted patients). Secondary endpoints were recurrence rate, disease-free survival (DFS), and toxicity. Results. The study included 77 patients. The conversion rate was 42% in the wild-type group compared to 51% in patients with a mutation. The cumulative recurrence rate in converted versus unconverted patients was 6% versus 32% (p = 0.005) translating into a three-year DFS of 94% versus 63% (p = 0.005). Conclusion. Neoadjuvant chemotherapy in colon cancer is feasible and the results suggest that a major part of the patients can be spared adjuvant chemotherapy. Validation in a randomized trial is warranted.